Fabrication and characterization of graphene hydrogel via hydrothermal approach as a scaffold for preliminary study of cell growth - Lim, H.N.; Huang, N.M.; Lim, S.; Harrison, I.; Chia, C.H. (2011)
Three-dimensional assembly of graphene hydrogel is rapidly attracting the interest of researchers because of its wide range of applications in energy storage, electronics, electrochemistry, and waste water treatment. Information on the use of graphene hydrogel for biological purposes is lacking, so we conducted a preliminary study to determine the suitability of graphene hydrogel as a substrate for cell growth, which could potentially be used as building blocks for biomolecules and tissue engineering applications. A three-dimensional structure of graphene hydrogel was prepared via a simple hydrothermal method using two-dimensional large-area graphene oxide nanosheets as a precursor. The concentration and lateral size of the graphene oxide nanosheets influenced the structure of the hydrogel. With larger-area graphene oxide nanosheets, the graphene hydrogel could be formed at a lower concentration. X-ray diffraction patterns revealed that the oxide functional groups on the graphene oxide nanosheets were reduced after hydrothermal treatment. The three-dimensional graphene hydrogel matrix was used as a scaffold for proliferation of a MG63 cell line. Guided filopodia protrusions of MG63 on the hydrogel were observed on the third day of cell culture, demonstrating compatibility of the graphene hydrogel structure for bioapplications.